The Effect of Venous Occlusion on the Sequestration of Blood Platelets - Hladovec, J; Koleilat, Z; Přerovský, I (Thrombosis and Haemostasis, 1972)
The venous occlusion of all four legs in rats caused a highly significant decrease of platelet counts in venous blood especially after the correction for an opposite change in haematocrit. A very pronounced decrease in platelets was observed in human volunteers after a venostasis in one arm in the blood drawn from the occluded limb just before the release of occlusion. Similar decreases were found after a venostasis of both legs in postocclusion blood samples. The decrease in blood platelets results from temporary sequestration in the occluded limbs. The decreases of platelets after a 10 min occlusion of both legs are more pronounced in patients with post thrombotic states.